Electric bike navigation behaviour in pedestrian crowds. (July 2020) - Kazemzadeh, Khashayar; Laureshyn, Aliaksei; Ronchi, Enrico; D'Agostino, Carmelo; Hiselius, Lena Winslott
Highlights: Highlighting the influence of pedestrian crowdedness on e-bike navigation behaviour. A fundamental relationship between e-bike speed and pedestrian crowdedness. Comparison of passing vs meeting conditions for a mixed traffic. Abstract: This study investigates the influence of pedestrian crowdedness on e-bike navigation behaviour in a controlled field experiment. The dataset includes a total of 1520 trajectories, including 18 pedestrians and one e-bike at a time. Based on the e-bike navigation through the pedestrians, the so-called "hindrance" concept was used to classify the data into two phases: passing (same-direction encounters), meeting (opposite-direction encounters). E-bike speed and its lateral position within the pedestrian crowds have been quantified to compare the passing and meeting phases. The results show that, the e-bike generally maintains an average speed during the meeting phase regardless of pedestrian crowdedness; however, the e-bike slows down in a linear trend when pedestrian crowdedness increases during the passing phase. Furthermore, the e-bike during the meeting phase has less lateral displacement compared to in the passing phase, which could be the consequence of the aforementioned speed and crowdedness relationship. The findings have applications for the e-bike level-of-service studies and also the design of bike tracks and sidewalks when there is mixed traffic of e-bikes and pedestrians.